Fasih Uddin. Pakistan under IMF Shadow. Islamabad: Institute of Policy Studies, 2008. Paperback. 128 pages. Price not given. (The Pakistan Development Review, 2009)
Pakistan like many other developing countries has been experiencing both financial and fiscal instability. This is mainly because it has miserably failed to generate sufficient resources required for its economic development. Consequently, to supplement its meager domestic resources, it has been mostly seeking foreign assistance. At times when ‘friends of Pakistan’, for their own ulterior motives, such as support for the cold war and war on terror, have helped Pakistan through project and programme aid, it has kept striving to move towards a higher path of economic growth despite poor governance and mismanagement of the economy by its planners and economic managers. At other times, when the ‘friends’ have been slow to coming forward, Pakistan has looked for financial aid from international financial institutions including the International Monetary Fund (IMF) and the World Bank. These institutions always attach stringent conditions to financial assistance. As a result, these institutions remain (implicitly) instrumental in the formulation of short- to medium-term economic policies of Pakistan, with outcomes that are always considered as sub-optimal.